Lentreprise Camerounaise Face Aux Financements Octroyes Par Les Institutions Internationales (Global Journal of Management and Business Research, 2020)
One can observe that inside States around the world, the meetings between enterprises, international institutions and foreign States become the occasion to conclude partnership aims to develop and to give international recognition to local enterprises. By doing so, Cameroonian enterprises may stand before financial sources coming from international institutions and foreign States. In fact, this situation let come in light a major opposition between communication and economic cooperation. In other words, is the meeting between enterprises an occasion to prepare an event with international institutions and foreign States or is this meeting an occasion to put in place mechanisms in favor of economic cooperation to ease the development of cameroonian enterprises?